Towards innovative public organizations: analyzing the e-government strategy in Demark and Algeria - Troudi , Hadjer; Bouhrour , Nour-El-Houda (Journal of Human Sciences, 2023)
The socio-economic society has undergone various unprecedented changes with the event of globalization, it marked by an enormous entry of technology into every aspect of everyday life; this has changed how people live, how companies deal with business and how governments satisfy citizen’s needs, so the use of ICTs can connect all three parties. In fact, most countries adopt policies that emphasize the use of these information and communication technologies in order to achieve better Electronic Government, consequently to increase citizen adoption and usage of their online government services. This paper aims to highlight the e-Government strategy in both developing and developed countries, taking the e-Algeria and the Danish experience as case studies.